Theoretical Predictions of Viscosity of Binary and Ternary Liquid Mixtures at 298.15 K - Singh, Vikash; Tiwari, K.K.; Singh, V.K. (Asian Journal of Chemistry, 2010)
Viscosities of five binary [cyclohexane (1) + carbon tetrachloride (2), benzene (1) + toluene (2), benzene (1) + cyclohexane (2), toluene (1) + carbon tetrachloride (2) and toluene (1) + cyclohexane (2)] and three ternary liquid mixtures [carbon tetrachloride (1) + cyclohexane (2) + benzene (3), toluene (1) + cyclohexane (2) + carbon tetrachloride (3) and benzene (1) + cyclohexane (2) + toluene (3)] at 298.15 K have been calculated using Frenkel relation, Kendall-Munroe relation, Bingham relation, Arrhenius-Eyring relation, Wassiljewa relation, Sutherland-Wassiljewa relation and Croenauer- Rothfus-Kermore relation. Validity of these relations has been checked by calculating average percentage deviations between calculated values and experimental values obtained from literature. Sutherland-Wassiljewa relation gives maximum deviations for all the systems in comparison to other methods employed. Other relations give comparatively good results.